Interobserver reproducibility of cervical lymph node measurements at CT in patients with head and neck squamous cell carcinoma. Issue 12 (December 2016) - Chung, M.S.; Cheng, K.L.; Choi, Y.J.; Roh, J.L.; Lee, Y.S.; Lee, S.S.; Lee, J.H.; Baek, J.H.
Abstract : Aim: To determine the interobserver reproducibility of measuring cervical lymph nodes at computed tomography (CT) in patients with head and neck squamous cell carcinoma (HNSCC) and to investigate the influence of finding extracapsular spread (ECS) at CT on measurement reliability. Materials and methods: The institutional review board approved the study protocol, and informed consent was obtained. A total of 146 patients with 224 suspicious lymph nodes underwent CT before treatment. Two observers independently measured the diameters (minimal axial, maximum axial, and maximum longitudinal diameter) and assessed the ECS using CT. The greatest diameter was defined as the largest among the three measured diameters. Interobserver variability was determined by the within-subject coefficient of variation, and interobserver agreement was determined by the intraclass correlation coefficient (ICC). Results: The within-subject coefficients of variation were 7.8%, 7.6%, and 11.4% for the minimal axial, maximum axial, and greatest diameters, respectively. The ICC values for interobserver agreement were excellent for all diameter measurements (i.e., ICC >0.9). Minimum and maximum axial diameter measurements were statistically more reliable than the greatest diameter measurement ( p =0.008 and p =0.0001, respectively). The presence of ECS on CT does not significantly affect the reliability of lymph node diameter measurements ( p> 0.05). Conclusion: Lymph node diameter measurement on CT is a highly reproducible and robust method. Additionally, imaging features of ECS do not affect reliability. Therefore, the measurement of lymph node diameter can be confidently performed in daily clinical practice or clinical trials. Highlights: Axial diameter measurements are more reliable than greatest diameter measurement. The interobserver variabilities in the axial diameter and greatest diameter are 7.8% and 11.4%, respectively. Extracapsular spread of lymph node on CT does not affect reliability of size measurement.